Development of the Orlan Space-Station antenna. - Tripp, Victor K. (IEEE Antennas & propagation magazine.)
The design of the Crew-Lock antenna for the Russian communication and data system [for the International Space Station] was challenging, because it is enclosed in a conducting shell. In addition, the electromagnetic-field distribution within the Crew Lock is highly constrained by the lowest one or two normal modes of the structure. Two kinds of antennas were investigated to address the requirements: a half loop and a loaded patch. Computer modeling of these approaches was done by the finite-element and moment methods, respectively. The loop antenna underwent extensive scale-model testing, and some full-scale tests at Johnson Space Center in Houston. The patch antenna was eliminated during the full-scale tests. The final design is the "towel-bar" loop, which performs the additional function of a handrail for astronauts during the ingress and egress for extra-vehicular activity (EVA).